The early years foundation stage: theory and practice - Palaiologou, Ioanna (Thousand Oaks: SAGE Publications, 2021)
'The EYFS affects all Early Years teaching, and is a core aspect of Early Years teaching and learning. This book provides students with a comprehensive and critical look at the EYFS curriculum. It encourages students to look at the theory and policy context behind the EYFS, and encourages them to relate it to practice through case studies and examples. It maps government policy directly onto different areas and requirements of teaching, giving students the opportunity to understand why different elements of teaching and curriculum are important'--
Includes index and references: 401-441.
Keywords: Early childhood education -- United Kingdom